Graft-Derived Cell-Free DNA as a Marker of Transplant Graft Injury. (April 2016) - Oellerich, Michael; Walson, Philip D.; Beck, Julia; Schmitz, Jessica; Kollmar, Otto; Schütz, Ekkehard
Abstract : Abstract: Although short-term success after solid organ transplantation is good, long-term graft and recipient survival are both not satisfactory. Despite therapeutic drug monitoring (TDM) of immunosuppressive drugs (ISDs), both excessive and insufficient immunosuppression still do occur. There is a need for new biomarkers that, when combined with TDM, can be used to provide more effective and less toxic, personalized immunosuppression to improve long-term survival. Currently used methods are insufficient to rapidly, cost-effectively, and directly interrogate graft integrity after solid organ transplantation. However, because organ transplants are also genome transplants, measurement of graft-derived circulating cell-free DNA (GcfDNA) has shown promise as a way to improve both graft and recipient outcomes after solid organ transplantation through the early detection of severe graft injury, enabling an early intervention. A newly developed droplet digital polymerase chain reaction (ddPCR) method has advantages over expensive high-throughput sequencing methods to rapidly quantify GcfDNA percentages and absolute amounts. This procedure does not require donor DNA and therefore can be applied to any organ donor/recipient pair. The droplet digital polymerase chain reaction method allows for the early, sensitive, specific, and cost-effective direct assessment of graft integrity and can be used to define individual responses to ISDs including the minimal ISD exposures necessary to prevent rejection. This is especially important in patients undergoing ISD switches due to ISD toxicity, infections, or malignancies. Although prospective, multicenter clinical trials in liver, heart, and kidney transplantation have not been completed, early results suggest that GcfDNA can be combined with TDM to guide changes in immunosuppression to provide more effective, and less toxic treatment. Personalized immunosuppression will shift emphasis in transplantation from reaction to prevention and could improve outcome at lower health care costs.